MODERN CHARACTERISTICS OF BULGARIAN BORDER TERRITORIES - Petkov, Veselin; Penerliev, Milen (Revista Inclusiones, 2021)
Border areas are an important part of the national geographical area of each country. They have the state border, cross-border opportunities and connections with neighboring countries. Often, they are an element of national security, given the fact that they are the location of military bases and facilities. In this context, it is important to characterize them as part of the hierarchical structure of the national geographical space, the development of settlements, the population and the specific border economy in them. This material attempts to do exactly this. To enable highlighing important problems in the development of such "marginal" areas. Bulgarian border territories are all administrative municipalities with a direct border with our neighboring countries by land or river. These include maritime communities. In this topic, the border, sea and Danube regions are artificially divided. The Danubeones are essentially part of the border areas.